The effect of remdesivir on selective biomarkers and its value in predicting the clinical outcome in patients with COVID-19 - Rai, Sanjana; Jones, Dyna; Jayashankar, Chinnappa Anjanappa; Kumar Pinnelli, Venkata Bharat; Manpreeth, Eashwer; Seetha, Venkata Sai Raghava Prashanthi (Asian Journal of Medical Sciences, 2021)
Background: To the best of our knowledge, there have been no studies to evaluate the effect of remdesivir on inflammatory markers. Aims and Objectives: To study the effect of Remdesivir on Selective biomarkers namely C-Reactive Protein (CRP), Lactate Dehydrogenase (LDH), Serum Ferritin and D-dimer and their value in predicting the clinical outcome in patients with COVID -19 infection. Materials and Methods: This is a retrospective observational study including 102 laboratory-confirmed COVID-19 patients of moderate and severe category who were subjected to complete blood count, liver function test, BUN, creatinine, C-reactive protein, lactate dehydrogenase, D-dimer, serum ferritin, ECG, and chest X-ray. The association was analyzed using independent sample t-test or Mann–Whitney U-test. Patients were divided into two groups. Both received corticosteroids and anticoagulants. Group A also received remdesivir. Results: Of the 102 patients, 90.2% of the patients in the non-remdesivir group and 94.1% in the remdesivir group were discharged. The mortality rate was 9.8% in the non-remdesivir group versus 5.9% in the remdesivir group (P=0.71). There was no statistically significant difference in the decrease of the inflammatory markers overtime in both the groups, irrespective of whether they received remdesivir or not. Conclusion: High values of the inflammatory markers were seen at the time of admission. A 5 days course of remdesivir failed to demonstrate a statistically significant difference in the decrease in the levels of the inflammatory markers. However, we have observed a possible clinical benefit of remdesivir among patients with moderate and severe COVID-19 disease, as there was a trend toward better clinical outcomes. Further studies are needed to evaluate this therapeutic strategy.